Variation of antioxidant and antibacterial activities of ethanolic extracts of propolis in three bee-keeping agro-ecological zones of Uganda - Kyomya, Julius; Kirabo, Mariam Kaanyi; Mayoka, Wilberforce John; Namunyenga, Rehema; Jaggwe, Rogers; Imanirampa, Lawrence; Tusiimire, Jonans (African Journal of Pharmacy and Pharmacology, 2023)
Propolis is a resinous plant material collected by bees to defend their colony. This study evaluated the antibacterial and antioxidant activities of ethanolic extracts of Ugandan propolis in three bee-keeping agro-ecological zones. Antibacterial assays were performed on two Gram-positive (S. aureus and S. pneumoniae) and two Gram-negative (E. coli and P. aeruginosa) bacteria within a concentration range of ~1.6 to 100 mg/ml. Antioxidant assays were conducted spectrophotometrically on the basis of DCPIP reduction and the attendant decrease in absorbance at 605 nm wavelength. All extracts showed antibacterial activity against S. aureus with MICs ranging from 2.8 to 200 mg/ml, but P. aeruginosa displayed susceptibility only for samples from Western Highlands (MIC = 9.5 mg/ml). Of the Gram-negatives, E. coli was the more susceptible organism (MICs 5.7-31.5 mg/ml), but S. pneumoniae was susceptible only to samples from mid northern and Lake Victoria Crescent (MIC 34.6 mg/ml). Samples from Mid Northern region exhibited the highest antioxidant activity (mean ± SD activity equivalent to 20.4±4.3 μg of ascorbic acid per mg of extract), while those from Western Highlands exhibited the lowest (mean ± SD activity equivalent to 8.9 ± 2.5 μg of ascorbic acid per mg of extract). The antibacterial and antioxidant activities of propolis varied within and, more significantly, between the agro-ecological zones. Taken together, these results highlight the potential of Ugandan propolis as an antioxidant and antibacterial agent. Strategic selection of hive localities in zones that offer the best output in propolis should be a priority for bee-farmers.
Keywords: Propolis; Agro-ecological zones; 2,6-dichlorophenolindophenol (DCPIP); Antibacterial; Antioxidant; Ascorbic acid; Apis mellifera